Genre and performance. - Cornea, Christine (Manchester University Press, 2017)
Looking at contemporary film and television, this book explores how popular genres frame our understanding of on-screen performance. It brings together ground-breaking and inspiring work on this topic from both renowned and newer academics in the field. Previous studies of screen performance have tended to fix upon star actors, directors, or programme makers, or they have concentrated upon particular training and acting styles. Moving outside of these confines, this book provides a truly interdisciplinary account of performance in film and television and examines a much neglected area in our u.